2022
DOI: 10.30595/pshms.v2i.223
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study: Trend in the Incidence of Tuberculosis Among Children in the Pekalongan

Abstract: Mycobacterium tuberculosis is the leading cause of death worldwide from a single bacterial pathogen. World Health Organization (WHO) estimates that annually, 1 million children have tuberculosis disease and many more harbor a latent form of infection. Evaluation of time trends is an integral part of a comprehensive analysis of tuberculosis among children data. Objective: This study aimed to assess trends in tuberculosis among children incidence in the period 2015-2021. Tuberculosis among data were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Furthermore, Noviyani et al (2021) mentioned that there was a rising trend of TB prevalence with age in the Indonesian population, with an estimated prevalence value of 759.1 per 100,000 population older than 15 years old. In addition, it was found that a total of around 33,336 cases of TB patients in Indonesia were acquired by children with an incidence rate of 2.52 cases per 1,000 populations by the year 2021 which is similar to the 2019 TB incidence rate in Pekalongan which reaches 2.21 cases per child population (Irnawati et al, 2022;Kementerian Kesehatan Republik Indonesia, 2021). It is also worth mentioning that higher TB prevalence was observed in urban areas compared to rural areas, which may indicate the significance of sociodemographic conditions to TB prevalence.…”
Section: Introductionmentioning
confidence: 75%
“…Furthermore, Noviyani et al (2021) mentioned that there was a rising trend of TB prevalence with age in the Indonesian population, with an estimated prevalence value of 759.1 per 100,000 population older than 15 years old. In addition, it was found that a total of around 33,336 cases of TB patients in Indonesia were acquired by children with an incidence rate of 2.52 cases per 1,000 populations by the year 2021 which is similar to the 2019 TB incidence rate in Pekalongan which reaches 2.21 cases per child population (Irnawati et al, 2022;Kementerian Kesehatan Republik Indonesia, 2021). It is also worth mentioning that higher TB prevalence was observed in urban areas compared to rural areas, which may indicate the significance of sociodemographic conditions to TB prevalence.…”
Section: Introductionmentioning
confidence: 75%